Gender differences in exercise stress testing protocol selection, exercise capacity, and prognostic value of METs. (25th November 2020) - Harb, S; Wang, T.W; Wu, Y.W; Menon, M.V; Cho, L.C; Cremer, P.C; Jaber, W.A.J
Abstract: Background: Exercise capacity, as measured by metabolic equivalents of task [METs], varies with gender and is an independent predictor of mortality. We sought to investigate gender differences in the protocol selected, the estimated exercise capacity, and the prognostic value of METs. Purpose: Investigate the gender differences in the protocol chosen (adjusting for age and comorbidities), the METs achieved (also adjusting for the protocol selected), and the predictive value of exercise capacity adjusted to METs achieved. Methods: In a 25-year stress testing registry spanning from 1991 to 2015, we identified 120, 705 patients who underwent exercise stress testing. Protocols were split into Bruce vs. non-Bruce. METs were estimated based on established gender-specific formulas (the St James Take Heart Project formula for women, and the Veterans Affairs cohort formula for men).The primary outcome was all-cause mortality. Results: The mean age was 53.3±12.5 years, and 59% were male. Table 1 presents the baseline characteristics and exercise parameters. A total of 8426 death occurred over 8.7 years of mean follow-up duration. Females were more commonly referred for non-Bruce protocols [adjusted OR 2.6; 95% CI (2.5–2.7)] even after adjusting for age and comorbidities. Within the same protocol chosen, females achieved lower estimated METs [Beta −1.4; 95% CI (−1.43 to −1.37)]. Exercise capacity was inversely related to mortality in both genders and across protocols (figure 1), however, after adjusting for age, comorbidities, protocol chosen, and the number of METs achieved, the HR for death was significantly lower for women [adjusted HR=0.44; 95% CI (0.41–0.46)]. Conclusion: After adjusting for age and comorbidities, women tend to be more commonly referred for non-Bruce protocols, achieve less estimated METs (after adjusting for the protocol chosen), and have half the mortality for the same METs achieved. Funding Acknowledgement: Type of funding source: None